Level of Cookery Competency Among 4’ps Mothers in Magtuod Davao City, Philippines: Basis for Intervention - Hinlayagan, Kymwell R. (Archives of Business Research, 2022)
The purpose of this study was to determine the level of cookery competency among 4’Ps mothers in Magtuod, Davao City. Descriptive correlational design was utilized in this study. The data were obtained from the 4’Ps mothers in Magtuod, Davao City, Philippines. The questionnaire used in this study is from the books of hygiene and sanitation and Cookery or Culinary Arts and Science. Mean was used to determine the level of cookery competency of 4’Ps Mothers of Magtuod, Maa, Davao City. Mann-Whitney U Test and The Welch’s ANOVA was used to determine the significant difference on the level of cookery competency of 4’Ps Mothers of Magtuod, Maa, Davao City. The Findings of the study revealed that the level of cookery competency of 4’Ps Mothers of Magtuod, Maa, Davao City in terms of food safety, menu composition and food preparation is moderate This means that the respondent moderately agrees with the embodied statement in each variable. Furthermore, there is no significant difference between food safety, menu composition, and food preparation when analyzed according to the age, number of children in the family and educational attainment of the respondents. This implies that food safety, menu composition, and food preparation are very important factors that needs to consider in preparing and cooking food for the family, thus the respondents of the study moderately understand its importance the result of this study is useful in developing a training program that may enhance and develop the knowledge and skills of the 4’Ps beneficiaries. Moreover, the result of the study shows that food safety, menu composition, and food preparation does not differ from the age, number of children in the family and educational attainment this indicates that knowledge and skills in basic food cooking can be learned and understand by different age generation even how many members in the family and educational attainment of the person.